Structure and Properties of Multiwall Carbon Nanotubes/Polystyrene Composites Prepared via Coagulation Precipitation Technique - I. N. Mazov; V. L. Kuznetsov; D. V. Krasnikov; N. A. Rudina; A. I. Romanenko; O. B. Anikeeva; V. I. Suslyaev; E. Yu. Korovin; V. A. Zhuravlev (Journal of Nanotechnology)
Coagulation technique was applied for preparation of multiwall carbon nanotube- (MWNT-)containing polystyrene (PSt) composite materials with different MWNT loading (0.5–10 wt.%). Scanning and transmission electron microscopies were used for investigation of the morphology and structure of produced composites. It was shown that synthesis of MWNT/PSt composites using coagulation technique allows one to obtain high dispersion degree of MWNT in the polymer matrix. According to microscopy data, composite powder consists of the polystyrene matrix forming spherical particles with diameter ca. 100–200 nm, and the surface of MWNT is strongly wetted by the polymer forming thin layer with 5–10 nm thickness. Electrical conductivity of MWNT/PSt composites was investigated using a four-probe technique. Observed electrical percolation threshold of composite materials is near to 10 wt.%, mainly due to the insulating polymer layer deposited on the surface of nanotubes. Electromagnetic response of prepared materials was investigated in broadband region (0.01–4 and 26–36 GHz). It was found that MWNT/PSt composites are almost radiotransparent for low frequency region and possess high absorbance of EM radiation at higher frequencies.